Hydrocortisone Fails to Abolish NF-κB1 Protein Nuclear Translocation in Deletion Allele Carriers of the NFKB1 Promoter Polymorphism (-94ins/delATTG) and Is Associated with Increased 30-Day Mortality in Septic Shock - Schäfer, Simon T. (Public Library of Science, 2014)
BACKGROUND: Previous investigations and meta-analyses on the effect of glucocorticoids on mortality in septic shock revealed mixed results. This heterogeneity might be evoked by genetic variations. Such candidate is a promoter polymorphism (-94ins/delATTG) of the gene encoding the ubiquitous transcription-factor nuclear-factor-κB (NF-κB) which binds to recognition elements in the promoter of several genes encoding for the innate immune-system. In turn, hydrocortisone inhibits NF-κB nuclear translocation and thus transcription of key immune-response regulators. Accordingly, we tested the hypotheses that hydrocortisone has a NFKB1 genotype dependent effect on 1) NF-κB1 nuclear translocation evoked by lipopolysaccharide (LPS) in monocytes in vitro, and 2) mortality in septic shock. METHODS: Monocytes of volunteers with the homozygous insertion (II; n = 5) or deletion (DD; n = 6) NFKB1 genotype were incubated with 10 µgml(-1) LPS ± hydrocortisone (10(-5)M), and NF-κB1 nuclear translocation was assessed (immunofluorescence). Furthermore, we analyzed 30-day-mortality in 160 patients with septic shock stratified for both genotype and hydrocortisone therapy. RESULTS: Hydrocortisone inhibited LPS induced nuclear translocation of NF-κB1 in II (25%±11;p = 0.0001) but not in DD genotypes (51%±15;p = n.s.). Onehundredandfour of 160 patients with septic shock received hydrocortisone, at the discretion of the intensivist. NFKB1 deletion allele carriers (ID/DD) receiving hydrocortisone had a much greater 30-day-mortality (57.6%) than II genotypes (24.4%; HR:3.18, 95%-CI:1.61-6.28;p = 0.001). In contrast, 30-day mortality was 22.2% in ID/DD and 25.0% in II genotypes without hydrocortisone therapy. Results were similar when using propensity score matching to account for possible bias in the intensivists' decision to administer hydrocortisone. CONCLUSION: Hydrocortisone fails to inhibit LPS induced nuclear NF-κB1 translocation in deletion allele carriers of the NFKB1 promoter polymorphism (-94ins/delATTG). In septic shock, hydrocortisone treatment is associated with markedly increased 30-day-mortality only in such carriers. Accordingly, previous heterogeneous results regarding the benefit of hydrocortisone in septic shock may be reconciled by genetic variation of the NFKB1 promoter polymorphism.